Komunikasi Persuasif Pada Pelaksanaan Advokasi Public Relations - Fathiya Nur Rahmi; Hanny Hafiar; Iriana Bakti (Program Studi Ilmu Komunikasi FISIP Universitas Syiah Kuala, 2019)
The awareness of job providers to employ people with disabilities is directly proportional to the participation of persons with disabilities in the formal work sector which is relatively low. Another problem faced by persons with disabilities is a negative stigma attached to them. This research was conducted to find out persuasive communication conducted on the Advocacy of LSM Saujana’s Public Relations, related to elements of communicators, messages, and audiences involved in persuasive communication. The research method used in this research is a case study with qualitative analysis techniques. Data collection techniques used in this study are interviews, observation, and documentation. Researchers conducted data analysis based on Flow Analysis Models. Based on the results, there were stages of persuasive communication undertaken including the preparation of communicators, delivery of messages, the use of online and offline media in delivering messages, the behavioral changes and evaluation. The LSM Saujana used the central route in persuasive communication that was appropriate to support advocacy. The findings suggest the institution focus on messages delivered to the target audience, starting with raising awareness and focusing on behavioral change.